Faktor-Faktor yang Berpengaruh Terhadap Penghindaran Pajak di Badan Usaha Milik Negara - Fitria Suciati; Sartika Wulandari (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The practice of tax avoidance is something that does not violate the law, but on the other hand the government does not want it because it will reduce state revenues. The purpose of this study was to analyze the effect of profitability, leverage, firm size, audit quality, independent commissioners, and institutional ownership on tax avoidance. This research is a quantitative research. Sample selection was done by purposive sampling method. The data used is secondary data with data analysis method using panel data regression analysis. The population of the data in this study are all state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The results of the study show that partially the size of the company and the independent commissioner have an effect on tax avoidance. Meanwhile, profitability, leverage, audit quality, and institutional ownership have no effect on tax avoidance. Simultaneously, profitability, leverage, firm size, audit quality, independent commissioners, and institutional ownership have an influence on tax avoidance. Keywords : Tax Avoidance, Size, Audit, Commissioners